Tinjauan Kesulitan Belajar Karena Gangguan Perkembangan (Autism, ADHD, dan Down Syndrome) - Habsy, Bakhrudin All; Azizah, Latif Nur; Aji, Oetari Zakiyah; Walidah, Zianah (Lembaga Yasin AlSys, 2024)
This research aims to identify the types of learning difficulties or obstacles that occur among students in the learning process and ways to overcome them. In this study, we employed the library research method. Learning difficulties refer to a condition where learners are unable to achieve the expected learning goals. These difficulties may arise due to developmental disorders. Developmental disorders are conditions in which an individual cannot develop normally, such as Autism, ADHD, and Down Syndrome. Identifying the forms of learning difficulties is crucial to be done early on if there are signs that do not align with a child's development. This is expected to enable the effective resolution of these difficulties by experts.